The Impact of the Arabic Literary Dialogue on the lengthy " Layla and Majnun " by Fuzuli Al-Baghdadi: A comparative study - Ibrahim, Shehab Gomaa; Iskandar, Youssef (Al-Adab Journal, 2021)
The study monitors the effect of the narrative dialogue component of Arabic literature in the lengthy " Layla and Majnun " by Fuzuli Al-Baghdadi, a comparative study, the research sheds light on two types of dialogue, the first of which is external dialogue, and the second is : self – dialogue, as they had a clear effect and influence between Arab literature and the length of the poet Fuzuli Al-Baghdadi to the point of a replica of dialogue in Arab literature as well as his artistic creativity.